Reflecting on Reflective Journals of Indonesian EFL Pre-Service Teachers to Examine Their Quality of Reflective Practice - M. Yoga Oktama; Endang Fauziati; Dewi Rochsantiningsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
Reflective practice is essential for teachers’ professional development. It leads teacher to shape and reshape their knowledge, and so forth a wide range of benefits can be achieved. However, to gain such benefits, teachers must have good quality of reflective practice. This qualitative case study aimed at investigating quality of reflective practice of four female EFL pre-service teachers in Indonesia. Framed with qualitative case study, this study employed online reflective journals as the main instrument to collect the data. The data were analysed deductively using content analysis. The results revealed that participants’ reflection tended to remain in the level of D1 and D2 which meant that they had tendency to merely retell and describe their teaching practice with limited evaluation. Only few of them were captured to reflect on the level of R1 and R2. In sum, although Indonesian EFL pre-service teachers had tendency to reflect in low level, it was interesting to find the fact that they sometimes reflected more critically in the level of R1 and R2. The result could be used as indicator that Indonesian EFL pre-service teachers had ability to reflect in a good way. Thus, following actions by related parties should be established in order to develop their abilities.